Mawewangsalan sebagai Media Komunikasi Masyarakat Abang Batu Dinding Kecamatan Kintamani Kabupaten Bangli - Yudhasatya Dharma, I Wayan; SM, Ulio (Institut Hindu Dharma Denpasar, 2020)
Human life cannot be separated from a communication, because human is a social creature whose lives depend on one another and communication is an intermediary between humans with one another. Through communication the attitudes and feelings of a person or group of people can be understood by other parties. In proportion to communication and language, a culture called Mawewangsalan emerged, which of course contained both elements, namely the use of language in communication systems as outlined into an art, namely the art of spoken words. Mawewangsalan culture is found in Abang Batu Dinding Village, Kintamani District, Bangli Regency. Mawewangsalan related to the form and nature in communication community in Abang Batu Dinding are two sentences that experience reduplication (lengkara kalih palet). The first sentence is like an insinuation, about heart of someone who says it, but has a hidden meaning behind words that are said. The second sentence is the true meaning of intend words. based on its nature Mawewangsalan can be divided into three, namely are jokes, advice, and figures of speech.The process of communication in Mawewangsalan conducted by the community in Abang Batu Dinding Village takes place in every situation and every place in the community's social environment. Mawewangsalan as a form of communication process in life of the community of Abang Batu Dinding Village has communication elements namely communicator, verbal code, and non-verbal code. In community of communication Mawewangsalan in Abang Batu Dinding Village has a cognitive impact, because in Mawewangsalan there are several things of educational values are contained. Affective effects also occur in this authority because it is able to influence attitudes and paradigm of people. As well as the impact of behavior is the next impact associated that changes in community behavior caused by the process of Mawewangsalan in the social life of the community.